2019
DOI: 10.1111/cid.12785
|View full text |Cite
|
Sign up to set email alerts
|

The thickness of labial bone affects the esthetics of immediate implant placement and provisionalization in the esthetic zone: A prospective cohort study

Abstract: Background A 1‐2 mm thick labial plate is generally advocated in immediate implant placement and provisionalization (IIPP). However, most of the human labial plates fail to meet this requirement. Purpose This study aimed to investigate the effect of labial plate thickness on hard tissue, soft tissue, and esthetic outcomes in IIPP. Materials and Methods In this prospective cohort study, 40 patients received IIPP of 50 single‐crown implants in the anterior maxilla. Patients were categorized into three groups acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
39
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(48 citation statements)
references
References 30 publications
(74 reference statements)
1
39
1
1
Order By: Relevance
“…All this suggests that by adding a CTG to thin gingival biotype sites, one may achieve similar outcomes as IIP at thick gingival biotype sites. In a recent study, it has also been shown that very thin buccal bone walls (<0.5 mm) suffer more resorption and mid‐facial recession (Yang et al, 2019). Finally, mid‐facial recession is more critical in the incisor/cuspid area due to aesthetic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…All this suggests that by adding a CTG to thin gingival biotype sites, one may achieve similar outcomes as IIP at thick gingival biotype sites. In a recent study, it has also been shown that very thin buccal bone walls (<0.5 mm) suffer more resorption and mid‐facial recession (Yang et al, 2019). Finally, mid‐facial recession is more critical in the incisor/cuspid area due to aesthetic reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, we can speculate that some of the volumetric outcomes of the alveolar ridge might be because of compensatory variations of the mucosa, has suggested by Chappuis et al 46 Despite of this, our study results are in accordance with several authors that emphatize the importance of the thin labial bone plate as a predictor factor for higher rates of mucosal recession and bone resorption around immediate implants inserted at the esthetic maxillary area. 47 Also, we must highlight the importance of a long-term follow-up of this treatment modality. Cosyn et al, concluded that after the 1-year evaluation, and despite the favourable early results obtained by immediate maxillary implants in terms of survival rate and MBL, mid-facial recession and mid-facial contour deterioration could be noticed.…”
Section: Discussionmentioning
confidence: 99%
“…It is noted that peri-implant tissue stability may be determined by the crestal bone thickness [16]. It is suggested that a 1 to 2 mm thick labial plate is necessary in immediate implant placement [17]. In another report, presurgical thickness of the labial bone was categorized as 0–0.5, 0.5–1, and ≥1 mm, and the esthetics of immediate implant placement was evaluated at 1 year follow-up; the results showed that more massive bone resorption and gingival recession were seen in groups with less than 0.5 mm thickness [17].…”
Section: Discussionmentioning
confidence: 99%